Mass‐forming type 1 autoimmune pancreatitis mimicking pancreatic cancer. Issue 3 (March 2016) - Hoshimoto, Sojun; Aiura, Koichi; Tanaka, Motomu; Shito, Masaya; Kakefuda, Toshihiro; Sugiura, Hitoshi
Abstract : We reported three cases of mass‐forming type 1 autoimmune pancreatitis (AIP) that were preoperatively suspected to be pancreatic cancer, and reviewed their clinicopathological features. Radiological findings in the patients revealed hypoattenuating masses in the early phase or a stricture of the main pancreatic duct with upstream dilatation, which was consistent with the diagnosis of pancreatic cancer. Histopathologically, the lesions were well demarcated and met all diagnostic criteria for immunoglobulin G4 (IgG4)‐related AIP, including the presence of periductal lymphoplasmacytic infiltration, obliterative phlebitis, storiform fibrosis and abundant IgG4‐positive plasma cells. However, the adjacent uninvolved pancreatic duct and lobular structures were well preserved. And in all patients, none or some of the aforementioned characteristics were observed. We suggest that some cases of focal AIP may progress to more severe grades and exhibit mass formation, although remaining localized. These focal cases of AIP are difficult to distinguish from pancreatic cancer. To our knowledge, this report is the first to present a histopathological comparison of mass‐forming AIP with the adjacent uninvolved pancreatic tissues.